Description and biomechanical evaluation of the modified laparoscopic-assisted percutaneous gastropexy technique in dogs - Kim, Dong Woo; Kwak, Ho Hyun; Kim, Junhyung; Woo, Heung Myong (Frontiers in Veterinary Science, 2025)
BackgroundTotal laparoscopic gastropexy (TLG) has become increasingly popular due to its minimally invasive nature, requiring only three ports and no additional skin incisions aside from those for port placement. However, a notable limitation of TLG is the difficulty and time required for intracorporeal suturing. To address this challenge, we investigated a new technique—modified laparoscopic-assisted percutaneous gastropexy (mLAPG)—in canine cadavers.Materials & methodsTwelve canine cadavers were divided into mLAPG (n = 6) and TLG (n = 6) groups. mLAPG was performed using a knotless barbed suture with two ports, and TLG was performed using a single-layer continuous barbed suture. Both methods employed a suture length of 3 cm and four suture bites. The total surgical time (TST) and gastropexy suturing time (GST) were recorded. Upon completion of the procedure, the stomach and body wall, including pexy site, were collected to evaluate the maximum load to failure of the gastropexies.ResultsNo significant differences were observed in the TST between the mLAPG (61.83 ± 4.80 min) and TLG (65.33 ± 12.05 min) groups (p = 0.538). The GST showed no significant difference between the mLAPG group (31.33 ± 3.13 min) and the TLG group (37.5 ± 7.06 min) (p = 0.095). The mLAPG group (35.86 ± 8.24 N) had a significantly higher maximum load to failure than the TLG group (24.04 ± 7.16 N) (p = 0.024).ConclusionThe results of this study suggest that the mLAPG, with its minimal invasiveness, absence of an intracorporeal suturing process, and high tensile strength can be clinically applied for gastropexy in dogs. However, further clinical trials are warranted to further validate this technique and confirm its effectiveness.